Retinopathy and clinical outcomes in patients with type 2 diabetes mellitus, chronic kidney disease, and anemia. Issue 1 (7th April 2014) - Bello, Natalie A; Pfeffer, Marc A; Skali, Hicham; McGill, Janet B; Rossert, Jerome; Olson, Kurt A; Weinrauch, Larry; Cooper, Mark E; de Zeeuw, Dick; Rossing, Peter; McMurray, John J V; Solomon, Scott D; et al.
Abstract : Objective: Retinopathy is an established microvascular complication of type 2 diabetes mellitus (T2DM), but its independent relationship with macrovascular and other microvascular complications is less well defined across the spectrum of kidney disease in T2DM. We examined the prognostic value of retinopathy in assessing the risk of developing end-stage renal disease (ESRD), cardiovascular morbidity or death among patients in the Trial to Reduce cardiovascular Events with Aranesp Therapy (TREAT). Design: TREAT enrolled 4038 patients with T2DM, chronic kidney disease (CKD) and moderate anemia. Patients were grouped by baseline history of retinopathy. Proportional hazards regression models were utilized to assess the association between retinopathy and subsequent ESRD, cardiovascular morbidity or death over an average of 2.4 years. Results: Although younger, the 1895 (47%) patients with retinopathy had longer duration of diabetes, lower estimated glomerular filtration rate, more proteinuria, and more microvascular complications. In univariate analysis, retinopathy was associated with a higher rate of ESRD, but not with cardiovascular events or mortality. After adjustment, retinopathy was no longer statistically significant for the prediction of ESRD or any clinical endpoint. Conclusions: In a large cohort of patients with T2DM, CKD, and anemia, retinopathy was common but not independently associated with a higher risk of renal or cardiovascular morbidity or death. Trial registration number: NCT00093015